2010
DOI: 10.1038/labinvest.2010.101
|View full text |Cite
|
Sign up to set email alerts
|

CCN1 induces a reversible epithelial–mesenchymal transition in gastric epithelial cells

Abstract: CCN1 is a matricellular protein that activates many genes related to wound healing and tissue remodeling in fibroblasts, but its effect on epithelial cells remains unclear. This study examined the role of CCN1 in epithelial wound healing using rat gastric epithelial cells and rat stomach ulcer as in vitro and in vivo models, respectively. We found that CCN1 expression is highly upregulated in the epithelial cells adjacent to a wound and remains high until the wound is healed. Upregulation of CCN1 activates a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
(55 reference statements)
0
23
0
Order By: Relevance
“…E-cadherin is a well-established “gate-keeper” for cell-adhesion and loss has been associated with epithelial mesenchymal transition and increased invasiveness [30][32]. Loss of E-cadherin in response to Cyr61 has been shown in Cyr61 induction studies in gastric cancer [33], however, we are among the first to report these findings in breast cancer.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…E-cadherin is a well-established “gate-keeper” for cell-adhesion and loss has been associated with epithelial mesenchymal transition and increased invasiveness [30][32]. Loss of E-cadherin in response to Cyr61 has been shown in Cyr61 induction studies in gastric cancer [33], however, we are among the first to report these findings in breast cancer.…”
Section: Discussionmentioning
confidence: 71%
“…Cyr61 has been shown to bind with integrins such as αvβ5 and α3β5, in the extracellular matrix space [37]. Integrin binding has been shown to induce actin filament rearrangement which can contribute to morphological changes- such as epithelial-mesenchymal transition [33]. Menendez and colleagues have demonstrated in several studies that targeting the αβ integrins in Cyr61 overexpressing breast cells successfully restores drug-response [26], [38].…”
Section: Discussionmentioning
confidence: 99%
“…Microarrays and immunohistochemical (IHC) stains were obtained as previously described (24,25), with formalin-fixed and paraffin-embedded 4-mm sections of the microarray, using the previously described (22,23,26) polyclonal anti-vimentin (positive control; 1:100 dilution), anti-UGT2B15 (1:300 dilution), and anti-UGT2B17 (1:150 dilution) antibodies (Supplementary SM2-8). The IHC staining (Supplementary SM2-8) was scored by a pathologist (L. Fazli) for the level of immunoexpression on a scale from 0 to 3, wherein 0 was undetectable, 1 represented a faint or focal questionably present stain, 2 represented a stain of convincing intensity in a minority of cells, and 3 represented a stain of convincing intensity in a majority of cells.…”
Section: Tissue Microarraysmentioning
confidence: 99%
“…In addition to being an angiogenic factor, CCN1 also supports cell adhesion, migration, proliferation, differentiation and survival. Recently, we have found that CCN1 is highly up-regulated in the gastric epithelial cells adjacent to the ulcer and remains high until the wound is healed (Figure 7; Chai et al, 2010b). This was demonstrated by epithelial injury both in vivo (gastric ulcer margin) and in vitro (gastric epithelial cell culture).…”
Section: Ccn1mentioning
confidence: 93%